Employee share schemes in Europe: The influence of US multinationals - Erik Poutsma; Paul E. M. Ligthart; Roel Schouteten (Management Revue, 2005)
The debate on convergence and globalisation of national economies emphasises the role of Multinational Corporations (MNCs) with regard to the export of homecountry policies in countries where they have their plants. MNCs set a process of change in motion in which local companies attempt to catch up with the more internationalised companies, particularly those from the Anglo-Saxon world. This process is called Anglo-Saxonisation. In this paper we focus on share (option) schemes. Analysing a European survey of HRM practices in workplaces in selected countries, we can trace a US-MNCs effect in the case of the narrow-based executive type of share (option) schemes in continental Europe. We can also trace a minor effect in the case of broad-based schemes open to all employees. The diversity we find in predictors between countries and the strong significant effects of country suggest that local corporate and institutional factors are more important in the case of broad-based share schemes than in the case of the narrow, executive type of share schemes.
Keywords: 650; employee share ownership; stock options; Human Resource Management; multinationals; Europe